The Vitalism and modern geographical thinking - Scarim, Paulo Cesar (Geografares, 2021)
Geographic thinking was at the center of philosophical and scientific formulations between the mid-18th century and the beginning of the 20th century. This period also represented a great influence of vitalist thinking. In this work we present elements to understand the relationship and mutual influence between vitalism and geographical thinking in this period of modern thought.